Islamic Book Publishing in Indonesia in the Cultural Industry Perspective - Mubarok Mubarok; Urip Mulyadi (Jurnal Ilmiah Komunikasi Makna, 2022)
AbstrakBuku merupakan jendela ilmu pengetahuan yang di dalamnya terkandung representasi beragam ideologi. Buku dengan konten Islami menjadi salah satu jenis buku yang mendominasi ruang baca di Indonesia. Buku berkonten Islami menjadi jembatan untuk mengkomunikasikan beragam ideologi, aliran, purifikasi agama, sosial, politik, ekonomi dalam pandangan Islam. Buku-buku tersebut membawa pengaruh yang signifikan dalam kehidupan masyarakat. Penelitian ini akan menguraikan perkembangan penerbitan buku Islami dimulai dari era 70 an, 80 an, dan masa reformasi sampai sekarang. Data diperoleh dari studi dokumen dalam bentuk artikel, buku, dan pemberitaan di media massa. Hal lain yang menarik adalah munculnya kekuatan aktor, fenomena buku terjemahan gratis yang disponsori beberapa negara dan kaitan antara industri buku yang berafiliasi dengan ideologi keagamaan tertentu. Menggunakan kerangka kritik industri budaya dari Theodore Adorno, data penelitian ditelaah dan dibahas. Kritik Adorno tentang industri budaya dalam industri penerbitan buku Islami di Indonesia mendapatkan kesesuainya. Meskipun demikian dalam tekanan industri budaya masih muncul karya-karya bermutu yang menjadi pembatal dari asumsi-asumsi kritik Adorno.Kata kunci : komunikasi, Islam, buku, konten, industri budaya  AbstractBooks are windows of knowledge in which there are representations of various ideologies. Books with Islamic content are one of the types of books that dominate reading rooms in Indonesia. Books with Islamic content become a bridge to communicate various ideologies, sects, religious purification, social, political, economic views of Islam. These books have had a significant impact on people's lives. This research will describe the development of Islamic book publishing starting from the era of the 70s, 80s, and the reformation period until now. Data were obtained from document studies in the form of articles, books, and reports in the mass media. Another interesting thing is the emergence of the power of actors, the phenomenon of free translation books sponsored by several countries and the link between the book industry which is affiliated with certain religious ideologies. Using Theodore Adorno's cultural industry critique framework, research data are analyzed and discussed. Adorno's critique of the cultural industry in the Islamic book publishing industry in Indonesia finds it appropriate. However, under pressure from the culture industry, quality works still emerge which invalidate Adorno's critical assumptions.Keywords: communication, Islam, books, content, culture industry